Analysis of Fe in pore water, solid phase and water column of different stations on the northwestern Black Sea shelf - Wytze K Lenstra; Martijn Hermans; Marie J M Séguret; Rob Witbaard; Thilo Behrends; Nikki Dijkstra; Niels A G M van Helmond; Peter Kraal; Patrick Laan; Micha J A Rijkenberg; Silke Severmann; Adrian Teaca; et al. (PANGAEA, 2018)
Continental shelf sediments are a major source of iron (Fe) for phytoplankton in surface waters. In this study, we investigate the mechanisms that control release of Fe from shelf sediments and its lateral transport (shuttling) in oxic and hypoxic waters on the northwestern Black Sea shelf. We find that at two coastal stations near the outflow of the Danube river high input of organic matterdrives strong reductive dissolution of Fe(oxyhydr)oxides (henceforth termed Fe oxides) in surface sediments, supporting high rates of Fe release to oxygenated bottom waters (0.36 mmol m-2d-1).We suggest that bioirrigation plays a key role in the release of Fe from these sediments. At four stations further offshore organic matter deposition is lower resulting in limited mobilization of Fe2+in the sediment and low benthic fluxes of Fe (<0.07 mmol m-2d-1). Lateral transport of Fe from the coastal zone towards the deep basin mostly takes place in colloidal and/or particulate form (>0.2μm) in the lower part of the water column, likely through repeated deposition and resuspension of Fe oxides from surface sediments. Using synchrotron-based X-ray spectroscopy and sequential chemical extractions, we demonstrate that the suspended matter and surface sediments are enriched in easily reducible Fe oxides (mostly ferrihydrite) and Fe associated with clay. The mobilization of Fe in the coastal zone and subsequent lateral transport of these Fe-bearing particles results in higher ratios of Fe/Al in surface sediments at outer shelf stations (ca. 1.2 to 2 wt% wt%-1) than at coastal stations (ca. 0.5 to 0.9 wt% wt%-1). However, below the sediment surface layer Fe/Al ratios are similar at all stations indicating limited burial of the laterally transported Fe. Our results highlight the critical role of organic matter input, associated biological activity and riverine Fe input as drivers of Fe shuttling on continental shelves. We also show that in shelf areas where sediments receive low inputs of organic matter, physical transport controls the ultimate fate of the shuttled Fe.
Supplement to: Lenstra, WK et al. (2019): The shelf-to-basin iron shuttle in the Black Sea revisited. Chemical Geology, 511, 314-341, https://doi.org/10.1016/j.chemgeo.2018.10.024